Implementasi Sistem Rekomendasi Pemilihan Jurusan dan Kampus Bagi Siswa SMA Berbasis AI - Falahah Falahah; Abdullah Fajar (Ikatan Ahli Informatika Indonesia, 2025)
Higher education plays a crucial role in determining one's future; however, many prospective students struggle to choose a major and university that align with their interests, talents, and future career prospects. A lack of comprehensive information and understanding of future job opportunities often leads to suboptimal choices. With the advancement of artificial intelligence (AI) and generative AI technology, decision-making in selecting majors and universities can be optimized using digital platforms that provide data-driven recommendations. Therefore, this community service program aims to assist prospective students in selecting the right major and university by using a web-based AI system. This community service program will be implemented over six months, with activities including application development, testing, outreach and implementation. The application will then be implemented among the target population, specifically students of grade X, SMA Negeri 17 Bandung. The program evaluation shows that the majority of students found the application engaging and easy to use, and that it significantly assisted them in determining suitable majors for their higher education.